Anatomical Characteristics of Cutaneous Branches Extending From the Second Dorsal Metacarpal Artery - Liu, Peng; Deng, Zhongyuan; Zhang, Tao; Li, Xiaojian (Frontiers in Bioengineering and Biotechnology, 2020)
Background A second dorsal metacarpal artery cutaneous branches flap is often used to repair skin defects in the hand. The location of the cutaneous branch of that artery is very critical for the removal of the flap. In this study, we quantitatively analyzed the origin of the cutaneous branches of the second dorsal metacarpalartery and the distribution characteristics of the radial and ulnar side to provide an anatomical basis for designing a flap. Methods Sixteen upper limb specimens were perfused with latex. Four specimens were infused with ethyl acetate plus plastic, and four specimens were perfused with red latex to create pellucid specimens. The origin, travel paths, and distribution of the cutaneous branches of the second dorsal metacarpal artery were anatomically observed, and we measured the length of the cutaneous branch from the midpoint of the second web space edge. We also measured the diameters and pedicle lengths of the radial and ulnar distributions of cutaneous branches of the second dorsal metacarpal artery. Results The cutaneous branches of the second dorsal metacarpal artery were mainly clustered at three positions, the second cluster point was at 43.9%, the fourth cluster point was at 61.2%, and the fifth cluster point was at 72.1%. The first cluster point was at 30.8% and the sixth cluster point was at 85.6%. The diameter and pedicle length of the sixth cluster point were the largest. There was no significant difference in the distribution of the diameters and pedicle lengths of the cutaneous branch between the radial and ulnar side. The second dorsal metacarpal artery sent out 1–2 cutaneous branches before the tendon joint, and formed a blood vessel anastomosis with other cutaneous branches located further from the tendon joint. The dorsal branch of the radial nerve in the hand extended a nerve branch at the wrist joint and traveled between the cutaneous branches of the second dorsal metacarpal artery to dominate the corresponding skin. Conclusion Three clusters in the distal second dorsal metacarpal artery were selected to be the flap pedicle containing a cutaneous nerve for use in repairing a skin defect in the hand and fingers.